IPO pricing in Singapore. - Goh, Li Yin. (2008)
This study examines the initial performance of IPOs listed on Singapore Stock Exchange (SES) Mainboard over a 10 year period from 1993 to July 2002. The objective is to investigate the effect of Asian Financial Crisis on the degree of underpricing.